A retrospective comparative study of CT and MRI findings of different types of pancreatic serous cystic neoplasms - Guangmang Li; Aichun Lei; Jianli Zhao; Peng Wang; Guanghai Ji; Xiao Han; Peng Li; Bo Li (Medicine, 2026)
A comparative analysis of the imaging and pathological findings across different types of serous cystic neoplasms (SCN) was conducted to delineate their distinct imaging characteristics and differentiate between various types of serous cystadenomas. This retrospective analysis included 65 patients diagnosed with SCN, categorized into macrocystic, microcystic, mixed, and solid types based on morphology. Imaging findings were compared across these types to elucidate their characteristics, and microscopic pathological observations were analyzed to identify differences among the SCN types. A total of 65 SCN patients (macrocystic, n = 18; mixed, n = 17; microcystic, n = 29; solid, n = 1) were analyzed. No significant differences were found in age, symptoms, or lesion location among subtypes ( P > .05), but mixed type lesions were significantly larger than microcystic type ( P < .05). Computed tomography (CT) and magnetic resonance imaging revealed distinct morphological and enhancement patterns: macrocystic type typically presented as unilocular or paucilocular cysts with no evident enhancement; mixed and microcystic types showed multiple cystic cavities, lobulated contours, fibrous central scars, and varying degrees of enhancement, with significantly higher precontrast CT values than the macrocystic type ( P < .05). The solid type (n = 1) exhibited a small, round mass with marked arterial enhancement and subsequent washout. Inter-observer agreement for CT quantitative parameters was excellent (intragroup correlation coefficient: 0.966–0.982). Imaging features including central scar, vascular displacement pattern, and margin characteristics differed significantly among subtypes ( P < .05), supporting the morphological classification of SCN. Light microscopy revealed that macrocystic types had large cyst cavities with thin fibrous septa, while microcystic types exhibited small cavities with dense fibrous septa. Mixed types presented a combination of both characteristics, and solid types showed very small cavities with abundant blood vessels. Imaging findings vary among different subtypes of SCN, and these differences are associated with their pathological features. The imaging characteristics are helpful for noninvasive differentiation of SCN subtypes and guidance of clinical decision-making.